Characteristics of Bacteriological Pulmonary Tuberculosis Cases for The January – August 2021 Period at Arifin Achmad Hospital, Riau Province - Rohani Lasmaria; Nidya Febrina; Arya Maganda Simanjutak (Syntax Corporation Indonesia, 2023)
Background: Mycobacterium tuberculosis, which causes TB, is a deadly disease that mostly affects the lungs. Surveys revealed that although there was significant variance, the estimated incidence of bacteriologically proven pulmonary TB per 100 000 people aged 15 or older was high in several countries. With multisectoral action and responsibility to address the larger causes that influence the TB epidemic and the socioeconomic effect of TB, knowing and comprehending the sociodemographic features of tuberculosis can serve as a milestone in the End TB Strategy by 2035. Methods: Descriptive cross-sectional methodology was employed in this study to collect data. 154 samples were collected over the course of eight months in accordance with the inclusion criteria; the findings are displayed as a distribution table. Results: The study's results showed that of 154 samples, patients with positive bacteriological TB were more likely to be men than women, to be in their prime working years, to be HIV-negative and to be medication sensitive. Discussion: Knowing characteristics of patients with pulmonary tuberculosis in important due to prevent higher risk of drug resistant, non-adherence treatment and mortality